Neuropeptide S reduces mouse aggressiveness in the resident/intruder test through selective activation of the neuropeptide S receptor. (October 2015) - Ruzza, Chiara; Asth, Laila; Guerrini, Remo; Trapella, Claudio; Gavioli, Elaine C.
Abstract: Neuropeptide S (NPS) regulates various biological functions by selectively activating the NPS receptor (NPSR). In particular NPS evokes robust anxiolytic-like effects in rodents together with a stimulant and arousal promoting action. The aim of the study was to investigate the effects of NPS on the aggressiveness of mice subjected to the resident/intruder test. Moreover the putative role played by the endogenous NPS/NPSR system in regulating mice aggressiveness was investigating using mice lacking the NPSR receptor (NPSR(−/−)) and the NPSR selective antagonists [ t Bu-D-Gly 5 ]NPS and SHA 68. NPS (0.01–1 nmol, icv) reduced, in a dose dependent manner, both the time that resident mice spent attacking the intruder mice and their number of attacks, producing pharmacological effects similar to those elicited by the standard anti-aggressive drug valproate (300 mg/kg, ip). This NPS effect was evident in NPSR wild type (NPSR(+/+)) mice but completely disappeared in NPSR(−/−) mice. Moreover, NPSR(−/−) mice displayed a significantly higher time spent attacking than NPSR(+/+) mice. [ t Bu-D-Gly 5 ]NPS (10 nmol, icv) did not change the behavior of mice in the resident/intruder test but completely counteracted NPS effects. SHA 68 (50 mg/kg, ip) was inactive per se and against NPS. In conclusion, this study demonstrated that NPS produces anti-aggressive effects in mice through the selective activation of NPSR and that the endogenous NPS/NPSR system can exert a role in the control of aggressiveness levels under the present experimental conditions. Highlights: The NPS effect in mice subjected to the resident/intruder test has been studied. NPS reduced the aggressiveness of mice in the resident/intruder test. NPS was totally inactive in NPSR(−/−) mice. NPSR(−/−) mice resulted more aggressive than NPSR(+/+) mice.